Activation of β(1) Integrins on Blood Eosinophils by P-Selectin - Johansson, Mats W. (American Thoracic Society, 2011)
Activation of β(1) integrins of blood eosinophils, assessed by mAb N29, correlates inversely with FEV(1) in two paradigms for studying control of human asthma. We asked whether P-selectin causes eosinophil β(1) integrin activation and results in increased adhesivity. By dual-label flow cytometry, eosinophils with high levels of surface-associated P-selectin had higher reactivity with the activation-sensitive anti-β(1) mAbs N29, 8E3, and 9EG7 than eosinophils with no or with a low-level of surface-associated P-selectin. Among patients with nonsevere asthma, surface P-selectin correlated with N29, 8E3, and 9EG7 signals. By immunofluorescence microscopy, surface-associated P-selectin was present in patches on eosinophils, some of which stained for the platelet marker thrombospondin-1. Activated β(1) and P-selectin partially colocalized on eosinophils. Soluble P-selectin added to whole blood enhanced activation of eosinophil β(1), but not β(2), integrins. In contrast, IL-5 activated eosinophil β(2), but not β(1), integrins. Eosinophils that did not attach to vascular cell adhesion molecule-1 (VCAM-1) in a static adhesion assay had a lower N29 signal than the original population. Soluble P-selectin added to whole blood enhanced eosinophil adhesion to VCAM-1. These findings are compatible with a scenario whereby P-selectin, on eosinophil-associated activated platelets or acquired from plasma or from prior interactions with endothelial cells or platelets, activates eosinophil α(4)β(1) integrin and stimulates eosinophils to adhere to VCAM-1 and move to the airway in asthma.